Navigating MSMEs success: A deep dive analysis of business success at Jogokaryan Mosque - Rarasati, Indin (JIFA (Journal of Islamic Finance and Accounting), 2025)
This study aims to analyze the influence of mosque-based microenterprise financing and empowerment programs on the business success of mustahiq (zakat recipients) at Jogokariyan Mosque. Recognized as a pioneer in the productive zakat management system, Jogokariyan Mosque integrates its financial initiatives with socio-religious programs such as benevolent loans (qardhul hasan), business training sessions (Ngaji Bisnis), and the creation of a community marketplace (Pasar Rakyat Jogokariyan). The originality of this research lies in its development of Abu Zahrah’s maqashid sharia framework by incorporating a new dimension—worship quality—which has not been addressed in previous studies.  The results reveal that financial wisdom and worship quality have a significant and positive effect on business success. Among these, worship quality demonstrates the strongest contribution, highlighting its importance as a spiritual dimension within the mosque empowerment model, followed by financial wisdom. This study concludes that the mosque-based empowerment model grounded in the maqashid sharia framework is effective in enhancing mustahiq business performance from both financial and spiritual perspectives. The findings reinforce the role of the mosque as a holistic and sustainable agent of socio-economic development and recommend the application of PLS-SEM as a robust approach for evaluating the success of productive zakat programs targeting microenterprises.